PENGUATAN KOMPETENSI PENGELOLA PERPUSTAKAAN MADRASAH DAN SEKOLAH MELALUI DIKLAT BERKESINAMBUNGAN - Fitri, Inda; Orina Fitri, Mega; Trinova, Zulvia (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
Education and training for madrasah and school library managers in the city of Padang to manage existing libraries should have an educational background in Library Science. In fact, the head of the library is a teacher in the field of study and the library manager is still honorary. Lack of attention from the leadership so that library managers are not creative because there is no continuous education and training. The questionnaire was distributed by the service team to 74 schools and madrasahs in the city of Padang and only 30 returned questionnaires, where the average school library accreditation score was very low and below the standard value of accreditation issued by the Jakarta National Library. This research-based service method is Participation Action Research (PAR) which involves parties from the Head of the West Sumatra Provincial Education Office, West Sumatra Provincial Archives and Libraries, the Head of the Ministry of Religion of Padang City is invited as a speaker. From the results of the education and training activities, it is not clear that the policies that will be carried out by leaders and decision makers to advance the library in a better direction.